The multifaceted roles of R2R3 transcription factor HlMYB7 in the regulation of flavonoid and bitter acids biosynthesis, development and biotic stress tolerance in hop (Humulus lupulus L.) - Mishra, Ajay Kumar; Kocábek, Tomáš; Nath, Vishnu Sukumari; Khan, Ahamed; Matoušek, Jaroslav; Hazzouri, Khaled M; Sudalaimuthuasari, Naganeeswaran; Krofta, Karel; Ludwig-Müller, Jutta; Amiri, Khaled M A (Plant physiology and biochemistry, 2023)
Hop (Humulus lupulus) biosynthesizes the highly economically valuable secondary metabolites, which include flavonoids, bitter acids, polyphenols and essential oils. These compounds have important pharmacological properties and are widely implicated in the brewing industry owing to bittering flavor, floral aroma and preservative activity. Our previous studies documented that ternary MYB-bHLH-WD40 (MBW) and binary WRKY1-WD40 (WW) protein complexes transcriptionally regulate the accumulation of bitter acid (BA) and prenylflavonoids (PF). In the present study, we investigated the regulatory functions of the R2R3-MYB repressor HlMYB7 transcription factor, which contains a conserved N-terminal domain along with the repressive motif EAR, in regulating the PF- and BA-biosynthetic pathway and their accumulation in hop. Constitutive expression of HlMYB7 resulted in transcriptional repression of structural genes involved in the terminal steps of biosynthesis of PF and BA, as well as stunted growth, delayed flowering, and reduced tolerance to viroid infection in hop. Furthermore, yeast two-hybrid and transient reporter assays revealed that HlMYB7 targets both PF and BA pathway genes and suppresses MBW and WW protein complexes. Heterologous expression of HlMYB7 leads to down-regulation of structural genes of flavonoid pathway in Arabidopsis thaliana, including a decrease in anthocyanin content in Nicotiana tabacum. The combined results from functional and transcriptomic analyses highlight the important role of HlMYB7 in fine-tuning and balancing the accumulation of secondary metabolites at the transcriptional level, thus offer a plausible target for metabolic engineering in hop.
Keywords: Transcription Factors; RNA sequencing; regulace genové exprese u rostlin; rostlinné proteiny; Flavonoids; Chalcone synthase; Gene Expression Regulation, Plant; Humulus lupulus; Plant Proteins; Bitter acids; Arabidopsis; R2R3 MYB; flavonoidy; Humulus; transkripční faktory